Implementation of the Program Keluarga Harapan (PKH) in Reducing Poverty and Preventing School Dropouts in Regions Great Aceh - Rahmi (Jurnal Serambi Ilmu, 2022)
In the many country the poor are still the main problem in the development.In the context of poverty alleviation, the government issued a program forhouseholds, namely the Program Keluarga Harapan (PKH). This study aimsto find out how the mechanism of PKH implementation in reducing povertyin Seulimum District, Aceh Besar District and to find out how the influenceof PKH in preventing dropouts in the community of Seulimum District,Aceh Besar District. The method used in this study is a qualitativedescriptive method. Based on the results of research that has been carriedout, it shows that the implementation of the Family Hope Program (PKH)has been going very well. This can be seen from every implementationprocess that runs smoothly. When viewed from the condition of therecipients of PKH assistance, they use it to overcome economic problemsand help children who are out of school, health and nutrition costs forpregnant women, postpartum mothers, and children under 6 years.